Spheroid Coculture of Human Gingiva-Derived Progenitor Cells With Endothelial Cells in Modified Platelet Lysate Hydrogels - Shanbhag, Siddharth; Rashad, Ahmad; Nymark, Ellen Helgeland; Suliman, Salwa; de Lange Davies, Catharina; Stavropoulos, Andreas; Bolstad, Anne Isine; Mustafa, Kamal (Frontiers in Bioengineering and Biotechnology, 2021)
Cell coculture strategies can promote angiogenesis within tissue engineering constructs. This study aimed to test the angiogenic potential of human umbilical vein endothelial cells (HUVEC) cocultured with gingiva-derived progenitor cells (GPC) as spheroids in a xeno-free environment. Human platelet lysate (HPL) was used as a cell culture supplement and as a hydrogel matrix (HPLG) for spheroid encapsulation. HUVEC and HUVEC+GPC (1:1 or 5:1) spheroids were encapsulated in various HPLG formulations. Angiogenesis was assessed via in vitro sprouting and in vivo chick chorioallantoic membrane (CAM) assays. HUVEC revealed characteristic in vitro sprouting in HPL/HPLG and this was significantly enhanced in cocultures with GPC (p<0.05). A trend for greater sprouting was observed in 5:1 vs. 1:1 HUVEC+GPC spheroids and in certain HPLG formulations (p>0.05). Both HUVEC and HUVEC+GPC spheroids in HPLG revealed abundant and comparable neoangiogenesis in the CAM assay (p>0.05). Spheroid coculture of HUVEC+GPC in HPLG represents a promising strategy to promote angiogenesis.